Comparison of Different Promoter Methylation Assays in Breast Cancer - Karijn P. M. Suijkerbuijk; Xiaojuan Pan; Elsken van der Wall; Paul J. van Diest; Marc Vooijs (Analytical Cellular Pathology)
Background: Promoter hypermethylation has emerged as a promising cancer biomarker. Currently, a large variety of quantitative and non-quantitative techniques is used to measure methylation in clinical specimens. Here we directly compared three commonly used methylation assays and assessed the influence of tissue fixation, target sequence location and the amount of DNA on their performance.